Characterization of KIR+ NK cell subsets with a monoclonal antibody selectively recognizing KIR2DL1 and blocking the specific interaction with HLA‐C. (15th May 2022) - Meazza, Raffaella; Falco, Michela; Canevali, Paolo; Loiacono, Fabrizio; Colomar‐Carando, Natalia; Muntasell, Aura; Rea, Anna; Mingari, Maria Cristina; Locatelli, Franco; Moretta, Lorenzo; Lopez‐Botet, Miguel; Pende, Daniela
Abstract : The phenotypic identification of different NK cell subsets allows more in‐depth characterization of KIR repertoire and function, which are of potential interest in KIR and disease association studies. KIR genes are highly polymorphic, but a great homology exists among the various sequences and few monoclonal antibodies (mAbs) specifically recognize a single KIR. This is the case of HP‐DM1 which was demonstrated by analysis of cell transfectants and epitope mapping to be exclusively KIR2DL1‐specific, covering all allotypes identified to date, except for KIR2DL1*022 and *020, and also to react with KIR2DS1*013. Here, we compared in immunofluorescence analyses the staining of HP‐DM1 with other available mAbs to precisely identify KIR2DL1 + NK cells in potential donors for αβT/B‐depleted haplo‐HSCT, with known KIR genotype. HP‐DM1 mAb was used in combination with EB6 or 11PB6 (anti‐KIR2DL1/S1 and anti‐KIR2DL3*005), 143211 (anti‐KIR2DL1/S5), and HP‐MA4 (anti‐KIR2DL1/S1/S3/S5) mAbs, allowing the accurate identification of different KIR + NK cell subsets. These phenotypic evaluations appeared useful to dissect the expression pattern of various KIR2D in NK cells from KIR2DL3*005 + individuals, particularly if KIR2DS1 is present. HP‐DM1 mAb remarkably refined NK cell phenotyping of donors carrying KIR2DS5, either in the centromeric or telomeric region. Functional assays with KIR2DL1 + /S1 + /S5 + NK cells confirmed that only HP‐DM1 exclusively reacts with KIR2DL1. Finally, we demonstrated that HP‐DM1 mAb blocked KIR2DL1 recognition of C2 + HLA‐C. Altogether, the data support that HP‐DM1 is a unique reagent valuable for characterizing KIR + NK cell subsets.